PENDAMPINGAN PENGUATAN LITERASI DASAR (MEMBACA, MENULIS, DAN BERHITUNG DI SDN 2 DUMAN - Muhammad Syawahid; Muhammad Rima Hamdani; M. Ardani Eka Julianto; Nurfadilah Nurfadilah; Fathira Ihda Alfinaini; Nurul Rahima; Annastasya Maharani Marzuki; Afifurrahman Afifurrahman (Fakultas Sains dan Teknologi, 2023)
International and national survey results categorize Indonesia as low in literacy skills. In order to improve literacy skills in schools, Kemdikbud launched the School Literacy Movement (GLS). To realize this goal, the Participatory Work Lecture (KKP) group of UIN Mataram were located in Duman Village, West Lombok implemented a basic literacy strengthening work program at SDN 2 Duman. The method used is participatory action research (PAR) which consists of problem identification, focus group discussion, implementation and evaluation. After the activities were carried out, the results obtained were an increase in students' basic literacy as shown by the ability to read, write and count for students who previously could not read, write and count. In addition, there was an increase in students' interest and motivation in reading, writing and counting. This activity also received a good response from students, teachers and the community with a satisfaction level percentage of 92.5%. Keywords: literacy, reading, writing, numeracy